Radio-resistance of hypoxic tumors: exploring the effects of oxygen and X-ray radiation on non-small lung cancer cell lines - Hanley, Rachel; Pagliari, Francesca; Garcia-Calderón, Daniel; Fernandes Guerreiro, Joana; Genard, Géraldine; Jansen, Jeannette; Nisticò, Clelia; Marafioti, Maria Grazia; Tirinato, Luca; Seco, Joao (Radiation oncology, 2023)
Solid tumors are often riddled with hypoxic areas, which develops as a result of high proliferation. Cancer cells willingly adapt and thrive in hypoxia by activating complex changes which contributes to survival and enhanced resistance to treatments, such as photon radiation. Photon radiation primarily relies on oxygen for the production of reactive oxygen species to induce DNA damage. The present in-vitro study aimed at investigating the biochemical responses of hypoxic non-small cell lung cancer (NSCLC) cells, particularly the effects on the DNA damage repair systems contributing to more radioresistant phenotypes and their pro- and anti-oxidant potential, within the first 24 h post-IR.
Gesehen am 14.06.2023